Analysis of Tourism Organization and Institution Responses to The Covid 19 Pandemic: Case Study in The Special Region of Yogyakarta - Damasdino, Fian (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The Covid-19 pandemic has had an extraordinary impact on the tourism sector. This paper examines tourism organizations and institutions in responding by studying data and actions that have been taken in the DIY area during the face of the Covid-19 pandemic. What tourism organizations and institutions have done in DIY can later be learned and can be adopted and applied in various regions in Indonesia. The research location focuses on the Special Region of Yogyakarta as one of the main tourism destinations in Indonesia. This study uses data collection methods in the form of primary data from field observations and interviews conducted directly by the authors, as well as using various secondary data from reports in local media in the DIY area. The author uses a qualitative descriptive data analysis method and content analysis (content analysis) on mass media coverage regarding organizational policies and tourism institutions in DIY. The results of the study show that tourism is one of the sectors that was greatly affected during the Covid-19 virus pandemic. Tourism organizations and institutions in DIY have prepared various programs so that tourism in this area can recover soon as before.